Ageing carers and intellectual disability: a scoping review. (29th August 2019) - Mahon, Aoife; Tilley, Elizabeth; Randhawa, Gurch; Pappas, Yannis; Vseteckova, Jitka
Abstract : Purpose: Individuals with intellectual disability(ies) are living longer contributing to an overall increase in the average age of caregivers. The purpose of this paper is to review the literature on the physical, social and psychological needs of ageing carers of individuals with intellectual disability(ies) in the UK. Design/methodology/approach: A scoping review framework was used to identify literature from eleven databases, the grey literature and the references lists of relevant studies. Only primary research studies that discussed the needs of non-professional carers, aged 65+ years old, of individuals with intellectual disability(ies) in the UK were included. No date restrictions were applied. Thematic analysis was used to narratively synthesise findings. Findings: Six studies were included. Five key themes were identified: Living with fear, lack of information, rebuilding trust, proactive professional involvement and being ignored. Housing and support information is not communicated well to carers. Professionals require more training on carer needs and trust must be rebuilt between carers and professionals. Proactive approaches would help identify carer needs, reduce marginalisation, help carers feel heard and reduce the risk of care crisis. Greater recognition of mutual caring relationships is needed. Originality/value: This review highlighted the needs of older caregivers for individuals with intellectual disability(ies) as well as the need for more high-quality research in this field. The information presented in this review may be considered by primary care providers and funding bodies when planning future support for this growing population of carers.